A New Zamilon-like Virophage Partial Genome Assembled from a Bioreactor Metagenome - Bekliz, Meriem; Verneau, Jonathan; Benamar, Samia; Raoult, Didier; La Scola, Bernard; Colson, Philippe (Frontiers in Microbiology, 2015)
Virophages replicate within viral factories inside the Acanthamoeba cytoplasm, and decrease the infectivity and replication of their associated giant viruses. Culture isolation and metagenome analyses have suggested that they are common in our environment. By screening metagenomic databases in search of amoebal viruses, we detected virophage-related sequences among sequences generated from the same non-aerated bioreactor metagenome as recently screened by another team for virophage capsid-encoding genes. We describe here the assembled partial genome of a virophage closely related to Zamilon, which infects Acanthamoeba with mimiviruses of lineages B and C but not A. Searches for sequences related to amoebal giant viruses, other Megavirales representatives and virophages were conducted using BLASTx against this bioreactor metagenome (PRJNA73603). Comparative genomic and phylogenetic analyses were performed using sequences from previously identified virophages. A total of 72 metagenome contigs generated from the bioreactor were identified as best matching with sequences from Megavirales representatives, mostly Pithovirus sibericum, pandoraviruses and amoebal mimiviruses from three lineages A-C, as well as from virophages. In addition, a partial genome from a Zamilon-like virophage, we named Zamilon 2, was assembled. This genome has a size of 6,716 base pairs, corresponding to 39% of the Zamilon genome, and comprises partial or full-length homologs for 15 Zamilon predicted open reading frames (ORFs). Mean nucleotide and amino acid identities for these 15 Zamilon 2 ORFs with their Zamilon counterparts were 89% (range, 81-96%) and 91% (range, 78-99%), respectively. Notably, these ORFs included two encoding a capsid protein and a packaging ATPase. Comparative genomics and phylogenetic analyses indicated that the partial genome was that of a new Zamilon-like virophage. Further studies are needed to gain better knowledge of the tropism and prevalence of virophages in our bio